AN ANALYSIS SOCIAL CHANGE IN OBAMA ERA AS REFLECTED LAUREN OLIVER’S NOVEL “BEFORE I FALL” - Neni Agustina; Risnawaty Risnawaty; Vera Kristiana (PHILOLOGY Journal of English Language and Literature, 2021)
This research is entitled “An Analysis Social Change In Obama Era As Reflected Lauren Oliver‟s Novel “Before I Fall. The purpose of this study is to determine what social changes occur in the novel “Before I Fall”. The method that has been used in this research is qualitative, because this method can provide accurate data. The data obtained from novel Before I Fall which consists seven chapters. Data is also taken from the books, journals and internet concerned with this research. The results showed that the social changes that occur have a positive impact that makes inspiration for adolescents and other society.